HOW STEM APPROACH THE DEVELOPMENT OF STUDENTS’ CRITICAL THINKING SKILLS IN SCIENCE EDUCATION? SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Nurmala Sari (Department of Physics Education, Faculty of Teacher Training and Education, UNIVERSITAS MA, 2026)
This systematic review attempts to close the gap by thoroughly examining the body of research to determine how well the STEM approach fosters students' critical thinking abilities. This study's methodology is a Systematic Literature Review, which yielded 224 papers from 2013 to 2025 by utilizing the keyword